The impact of oil price shocks on Islamic financial market in Malaysia - Mohd Hussin Mohd Yahya, Muhammad Fidlizan, Noordin Kamaruzaman, Marwan Nur Fakhzan, Abdul Razak Azila (N/A, 2012)
The impact of oil price shocks on Islamic financial market in Malaysia by Mohd Hussin Mohd Yahya, Muhammad Fidlizan, Noordin Kamaruzaman, Marwan Nur Fakhzan, Abdul Razak Azila,